Regioselective Benzylic C–H Alumination and Further Functionalization of 2‑Alkylpyridines by Yttrium Catalyst - Takimoto, Masanori; Liu, Mingyu; Nishiura, Masayoshi; Hou, Zhaomin (ACS catalysis, 2022)
The regioselective benzylic C–H alumination of various symmetrical and nonsymmetrical 2,6-alkylpyridines catalyzed by a half-sandwich yttrium complex has been developed. The resulting alkylaluminum species bearing a pyridyl ring moiety can be transformed to the corresponding alcohols by oxidation. Moreover, the Cu-catalyzed allylation and benzylation and Pd-catalyzed arylation reactions can be applied to the resulting alkylaluminum species, giving the corresponding α-mono-allylated, α-mono-benzylated, and α-mono-arylated 2-alkylpyridine derivatives, respectively, in good to high yields. Unsymmetrically substituted 2,6-dialkylpyridines can be synthesized from simple symmetrical substrates by repeating such C–H alumination/C–C bond formation processes. Because of the high regioselectivity of the present C–H alumination and the subsequent C–C bond formation, this protocol may serve as a desirable method for the synthesis of nonsymmetrically-2,6-disubstituted pyridine derivatives.